2005
DOI: 10.1590/s0080-62342005000200010
|View full text |Cite
|
Sign up to set email alerts
|

Assistência individualizada: posso trazer meu cachorro?

Abstract: Estudo de caso com objetivo de conhecer a percepção de uma adolescente portadora de leucemia linfocítica aguda recidivada e da sua mãe sobre a visita do seu cão de estimação durante a hospitalização, bem como descrever a experiência enquanto intervenção de enfermagem. Os dados foram obtidos e organizados mediante relato de experiência. Benefícios dessa medida terapêutica foram observados demonstrando que a Terapia Assistida por Animais deve ter sua utilização ampliada para outras situações clínicas, constituin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 8 publications
0
11
0
7
Order By: Relevance
“…The parents/companions must also address feelings of powerlessness, changes in their routine, and giving up the comfort of their homes. The dog can also help them face the disease and treatment (Bussotti et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parents/companions must also address feelings of powerlessness, changes in their routine, and giving up the comfort of their homes. The dog can also help them face the disease and treatment (Bussotti et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In a case report, a hospitalized child requested the company of their own dog, which shows that AAT provides therapeutic benefits to the patient's psychological health by providing moments of relaxation and humanized assistance for both the patient and their family (Bussotti et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The ATD can be used by a nurse to help in the child's adaptation to stressful situations, increase mobility and muscular activity, and promote the child's collaboration during procedures, considering they tend to feel more relaxed and confident when realizing the hospital environment also provides them pleasant and fun moments (7) . Nurses consistently search for interventions to reduce the stress of hospitalization and to make the treatment of cancer easier; for this reason, in health care, the use of alternative therapies capable of developing strategies to make this process less traumatic has been valued (5,8) . A case study carried out in São Paulo showed that the development of a care plan involving AAT and ATD can provide moments of relaxation and joy, which benefits the patient, the person accompanying the patient, the patient's family, and also the nursing staff (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Nurses consistently search for interventions to reduce the stress of hospitalization and to make the treatment of cancer easier; for this reason, in health care, the use of alternative therapies capable of developing strategies to make this process less traumatic has been valued (5,8) . A case study carried out in São Paulo showed that the development of a care plan involving AAT and ATD can provide moments of relaxation and joy, which benefits the patient, the person accompanying the patient, the patient's family, and also the nursing staff (8) . Despite all the advantages evidenced by this therapy, health professionals and relatives still have a lot of insecurities regarding this practice mainly when it comes to children with cancer, considering opportunistic infections can emerge depending on the immunosuppression status.…”
Section: Introductionmentioning
confidence: 99%
“…Com base na investigação de pesquisas sobre as IAAs, locais vem aderindo esse tipo de intervenção como hospitais, lares de idosos, unidades de cuidados paliativos, estabelecimentos de saúde mental, escolas, presídios e apresentando propostas de melhoria no humor, motivação, autoestima e bem-estar físico e psicológico dos envolvidos 2,3 . Os efeitos positivos dessas abordagens se ampliam nos campos da saúde e da educação, tais como: diminuição da ansiedade 7 ; diminuição nos níveis de cortisol e adrenalina e aumento dos níveis de ocitocinas (hormônios associados ao estresse) 8 ; auxiliar em tratamentos de saúde e da socialização 9 ; melhora no enfrentamento da doença 10 ; aumento do bem-estar e conforto em crianças hospitalizadas…”
unclassified